Defining community: A pragmatic political ecology approach - Jessica Mikels; Rachel Menale (Environmental and Sustainability Indicators)
There is a growing recognition of the need to bridge the ecological and the social to best respond to the myriad of socio-environmental challenges of the Anthropocene. While this recognition has grown, we often lack the language for non-dualistic thinking of all species’ needs. In this brief, theory-focused piece, we propose a non-dualistic definition of community that may provide an orienting framework toward a more inclusive and holistic idea of community in community conservation. This concept aims to simultaneously consider both human and more-than-human species, linking human environmental justice with the conservation of more-than-human species through the lens of Pragmatic Political Ecology. We outline the philosophical foundations of this idea, develop indicators for assessing if projects meet the definition proposed, and provide examples of existing work that utilize this approach in community conservation.